1985
DOI: 10.1111/j.1476-5381.1985.tb12942.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for neuro‐effector transmission through postjunctional α2‐adrenoceptors in human saphenous vein

Abstract: 1The effects of the ax-adrenoceptor antagonist prazosin and the x2-adrenoceptor antagonist yohimbine were examined against stimulation-evoked contractions in human isolated saphenous veins.2 The concentration of yohimbine producing 30% inhibition of stimulation-evoked contractions (IC30) was 13.2 nM, whereas the IC30 of prazosin was greater than 250 nM. 3 The inhibition of stimulation-evoked contractions by yohimbine was not prejunctionally mediated since yohimbine (0.01-0. I IM) significantly potentiated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 15 publications
5
21
0
Order By: Relevance
“…The identity of the other component is discussed below. Docherty & Hyland, 1985b). The pA2 of 6.36 obtained for yohimbine in the absence of cocaine is similar to the pA2 of 6.56 obtained at a1-adrenoceptors in the rabbit pulmonary artery (Weitzell et al, 1979).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The identity of the other component is discussed below. Docherty & Hyland, 1985b). The pA2 of 6.36 obtained for yohimbine in the absence of cocaine is similar to the pA2 of 6.56 obtained at a1-adrenoceptors in the rabbit pulmonary artery (Weitzell et al, 1979).…”
Section: Discussionsupporting
confidence: 62%
“…Muller-Schweinitzer (1984), also using the human isolated saphenous vein, found that yohimbine was approximately 60 times less potent against 5-HT than against NA. The higher pA2 of 7.06 obtained for yohimbine against NA in the presence of cocaine suggests that M2-adrenoceptormediated effects become more marked when uptake blockade allows access to the junctional receptors which are x2-receptors (Docherty & Hyland, 1985b).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the most striking finding of this study was that a2-adrenoceptors play a major role in mediating the vasoconstrictor responses to m-agonists and nerve stimulation, whereas in previous in vitro studies these responses were predominantly mediated by a,-adrenoceptors (Ferrell & Khoshbaten, 1989;1990a Docherty, 1989 (Docherty & Hyland, 1985). It could be argued that the difference in the results obtained in the in vitro and in vivo preparations may be related to different methodologies.…”
Section: Discussionmentioning
confidence: 48%
“…Contractions to noradrenaline and nerve stimulationevoked contractions in the human saphenous vein are mediated predominantly by X2-adrenoceptors based both on the absolute and relative potencies of yohimbine and prazosin (Muller-Schweinitzer, 1984;Steen et al, 1984;Docherty & Hyland, 1985;Docherty, 1987 (Bylund, 1985;, this might suggest that all the a2-adrenoceptors examined in this study resemble the CA2A, based on absolute potency of prazosin. However, when potency of prazosin is expressed relative to yohimbine, prazosin is 20 (rat vas deferens), 9 (human saphenous vein) or 8 (rat atrium) times less potent than yohimbine in our functional studies, similar to the potency ratio found by Bylund for the a2B subtype as in neonatal rat lung or for the a2c subtype as in the OK cell line (Murphy & Bylund, 1988) with high affinity for prazosin (5-7.6nM), but prazosin was 260 times less potent than yohimbine at the a2A of human platelet (present data and Bylund, 1988).…”
Section: Discussionmentioning
confidence: 73%